Penggunaan Modul Komunikasi Keluarga Sebagai Salah Satu Model Pengasuhan Keluarga Bagi Siswa SMP 1, 2, 3 Sukawati Gianyar - N.L.P Yunianti Suntari C; NLK Sulisna Dewi; I Ketut Labir (Poltekkes Kemenkes Denpasar, 2019)
Children are infinite gifts. They are the next generation of the nation in a country. Children's growth and development is an absolute concern for parents. To achieve good growth and development of children, of course also must be with education and support from the environment where children live. Children are complex creatures who have a high dependence on other people, especially the closest person. Information and guidance for parents, we pack in a simple book, with the titled